Research in geography - Chaturvedi, D. D., 1936- (New Delhi : Anmol Publications, 1993)
Bibliography of Ph. D. degrees awarded in geography by the Indian universities from the beginning to 1991.
Includes index.
Keywords: Geography -- Bibliography; Dissertations, Academic -- India -- Bibliography